SARS-CoV-2 Viral Shedding and Associated Factors among COVID-19 Inpatients and Outpatients - Masoomeh Sofian; Behzad Khansarinejad; Ehsanollah Ghaznavi-Rad; Farzaneh Shokoohi; Hossein Mazaherpour; Farzane Farmani; Mona Sadat Larijani; Leila Pakpour; Amitis Ramezani (Interdisciplinary Perspectives on Infectious Diseases)
Background. According to the contagious ability of the new virus, SARS-CoV-2, characterization of viral shedding duration in the period of infection is highly valuable in terms of providing quarantine guidelines and isolation policies. Therefore, we aimed at viral shedding determination in 58 COVID-19 confirmed Iranian subjects in different stages. Methods. 58 COVID-19 confirmed Iranian subjects including 21 outpatients and 37 inpatients were investigated. The analytical data and clinical properties were documented in the standard questionnaire. The RT-PCR tests were done two and three weeks after the symptoms initiation. Results. Viral eradication occurred in 44.8% two weeks after illness initiation whereas in 71% who achieved a negative PCR test in the third week. Moreover, prolonged viral shedding was observed in hospitalized cases in comparison to outpatients. Almost 30% of patients continued viral shedding three weeks after disease initiation. Conclusion. A longer duration of viral shedding in hospitalized cases rather than outpatients was observed in this study. The results similar to other investigations call into question if the current policies are enough to prevent the viral spread or not. This study should be done on a larger sample to provide an appropriate time in isolation policy.